Knowledge, Attitude and Practice Regarding Kidney Diseases among Primary Care Physicians working in Nepal - Nepal, Richa; Bhattarai, Bharosha; Bhandari, Abhishek; Adhikari, Bishow Nath; Nepal, Rhishikesh; Khanal, Nimesh (Journal of Advances in Internal Medicine, 2022)
Background: Medical officers and resident doctors as primary care physicians (PCPs) are the first contact health care providers to most of the kidney disease patients in Nepal. This study intends to assess knowledge, attitude and practice regarding kidney diseases among these nonnephrology doctors, working in different health institutes all over Nepal. Methods: This was a descriptive, cross sectional, questionnaire based study, conducted over the span of 12 weeks among the primary care physicians. The Ethical Review Board of Nepal Health Research Council had approved our protocol prior to starting the study. An arbitrary scoring system was used to classify knowledge, attitude and practice scores as: 0 to <50% - Poor score, 50% to <75% - Moderate score, ≥ 75% - Good score. Data was entered in Microsoft Excel and analyzed using IBM Statistical Package for the Social Sciences version 25. Results: Out of 239 PCPs enrolled in our study, 41 (17%) obtained good knowledge scores, 124 (51.8%) obtained good attitude scores and 198 (82.8%) obtained good practice scores. None of the study participants had negative attitude towards kidney diseases. The mean scores obtained in our study were 23.03±4.49 for knowledge, 17.64±2.30 for attitude and 6.27±1.24 for practice domains out of total score of 37, 24, and 8 respectively. Conclusions: Our study demonstrated that the majority of PCPs had obtained moderate to poor knowledge scores regarding kidney diseases. However, the majority had a positive attitude and good practice regarding kidney diseases in our study.